Statistical analysis using SPSS Version 24 - Wan Ahmad, Wan Muhamad Amir; Mohd Ibrahim, Mohamad Shafiq; Abdul Halim, Nurfadhlina; Aleng @ Mohamad, Nor Azlida (Penerbit Universiti Sains Malaysia, 2019)
This book provides the best solution for students and researchers in understanding the basic concept and the right procedure for the data analysis. The main objective of this book is to guide and help students or researchers who are using Statistical Package for the Social Sciences (SPSS) software in performing the statistical methods in their applied research. This book is very easy to follow for beginners in SPSS by following simple step-by-step instructions. It is arranged in a way that it is user friendly, and is written in a simple language that can easily be understood by the users. This book will give a straightforward solution to students and can also be used as a guideline in performing the statistical test using statistical analysis tools. Hopefully this book will help students in making good presentations and conclusions based on the results obtained and provides valuable information on statistical methods in applied research.